Variación espacio-temporal del ph en la microcuenca del Río Cutuchi utilizando técnicas de estimación geoestadística. - Espín Villalva, Evelin Micaela (2018)
The present research evaluated the variation space-temporary of the pH concentrations in Cutuchi River Microbasin (CRM), which is part of the Pastaza River, the CRM is born in the moors of Cotopaxi volcano thaws, it has an area of 2677 km2 and 60 km length. The contamination of the rivers when mentioning the pH indicator is caused by the high concentrations of metals such as manganese and iron, potentially corrosive metals of the pipes in the old houses, which later they trigger in the River. For the investigation , two databases were used, one by Technical University of Cotopaxi (UTC) and other by International University (SEK), which were monitored since September 2010 to July 2011 by UTC, and by SEK since October to April 2017. Initially, an exploratory data analysis (EAD) it was carried out to evaluate the distribution and behavior of data, which were subsequently begind with the Surfer interpolator package and finally to realize the spatial distribution maps of the pH in the CRM. As a result, it was obtained in the exploratory analysis data (EAD) that the it presented little outliers and completed with the criterion of the mean were interpolated to obtain the three best interpolators: Polynomial regression, moving averages and Kriging for the two databases which were evaluated with the mean square error (CRM). It was concluded that the best interpolators obtained pH data in the Cutuchi River Microbasin (MRC), which were not monitored and predict their distribution behavior, thus decreasing costs of time and money required for the collection of information from countryside.